Hip Fracture Care: Perioperative and Rehabilitative Management - Ed Vandenberg; Kate Twenter; Matt Mormino (Association of American Medical Colleges, 2010)
Abstract This resource addresses key issues in hip fracture management. It is divided into three modules: preoperative evaluation, postoperative care, and hospital/posthospital rehabilitation. The target audience is in-training and postgraduate health care professionals in the following disciplines: physicians, physician assistants, nurse practitioners, physical therapists, and pharmacists. The unit is accredited for 1 hour of continuing education for any of the disciplines mentioned, with the projected time to complete all three modules approximately 1 hour. Primarily designed for distance education with voice overlay, each of the three modules was developed to be completed in 15 to 20 minutes, followed by posttest questions. This format of short, concise educational interventions fits well into the practice life of busy health care professionals. These modules address a common, complex problem in geriatric care. They were reviewed by academic peers in our institution and completed online by 50 practicing health care providers in the Nebraska Geriatric Educational Center's mini-fellowship in geriatrics. Evaluations were excellent, and the distance-based learners appreciated the content and the format. We also utilized a satisfaction survey at the end of the unit to obtain learners' opinions. In this postsurvey, the question "Were this module's learning objectives met?" received a 98% response of yes. Replies to the open-ended questions were utilized for improvement. There was limited constructive criticism, most of the replies revolving around technical difficulties learners experienced. The entire unit or individual modules can be given as live presentations, utilizing the script placed in the notes section of the PowerPoint to assist in presentation. The modules have also been utilized as a stand-alone read-only format, where the learner views the slides and reads the explanatory script in the notes section. Additionally, each individual module can function as a stand-alone for specific disciplines, such as physical therapy students reviewing only the module on rehabilitation. The modular format is concise and partialized, allowing presenters to select the most relevant information for their audience. Regarding use in distance learning, our feedback is that the 15-to 20-minute segments are popular; the learners indicate that the postmodule questions create a break and closure and that the 1-hour credit for completion of the three-module unit is attained painlessly.